Phenotypic Bacterial Isolates, Antimicrobial Susceptibility pattern and Associated factors among Septicemia Suspected Patients at a hospital, in Northwest Ethiopia: Prospective cross-sectional study - Habtamu Belew; Workineh Tamir; Tebelay Dilnessa; Abeba Mengist (BMC, 2023)
Abstract Background Septicemia is potentially fatal infection caused by pathogenic bacteria infiltrating the bloodstream, resulting in morbidity and mortality among Ethiopian hospital patients. Multidrug resistance is a therapeutic challenge in this patient population. There is an insufficiency data among hospitals in Ethiopia. Hence, this study aimed to assess the phenotypic bacterial isolates, antimicrobial susceptibility pattern, and associated factors among septicemia suspected patients. Methods Prospective cross-sectional study was conducted among 214 septicemia suspected patients from February to June 2021 at Debre Markos Comprehensive Specialized hospital in northwest, Ethiopia. Blood samples were collected aseptically and processed to identify bacterial isolates by using different standard microbiological procedures. Antimicrobial susceptibility pattern was performed using the modified Kirby Bauer disc diffusion on Mueller Hinton agar. Epi-data V4.2 was used to enter data and SPSS V25 for analysis. The variables were assessed using a bivariate logistic regression model with a 95% confidence interval, and declared statistically significant; P-value was < 0.05. Results The overall bacterial isolates was found 45/214 (21%) in this study. Gram-negative and positive bacteria were 25/45(55.6%), 20/45(44.4%) respectively. The most common bacterial isolates were Staphylococcus aureus12/45 (26.7%), Klebsiella pneumoniae 8/45(17.8%), Escherichia coli 6/45 (13.3%). Gram-negative bacteria showed susceptibility to amikacin (88%), meropenem, imipenem (76%) but, (92%) resistance to ampicillin, (85.7%) amoxicillin-clavulanic acid. S.aureus (91.7%) was resistance to Penicillin, (58.3%) cefoxitin and (75%) susceptible to ciprofloxacillin. S.pyogenes and S.agalactia were (100%) susceptible to Vancomacin. Multidrug resistance was found in 27/45(60%) of the bacterial isolates. The main predictors related to patients suspected of septicemia were prolonged hospitalization (AOR = 2.29, 95% CI: 1.18, 7.22), fever (AOR = 0.39, 95%CI: 0.18, 0.85) and length of hospital stay (AOR = 0.13, 95%CI: 0.02, 0.82). Conclusions Incidence of bacterial isolates among septicemia suspected patients were high. The majority of the bacterial isolates were multidrug-resistant. To prevent antimicrobial resistance, specific antibiotic utilization strategy should be applied.